Acute subjective response to alcohol as a function of reward and punishment sensitivity. (September 2016) - Morris, David H.; Treloar, Hayley; Tsai, Chia-Lin; McCarty, Kayleigh N.; McCarthy, Denis M.
Abstract: Individual differences in subjective response to alcohol play a crucial role in the development of heavy drinking and related problems. In light of this, a growing focus of research has been identifying factors that contribute to differences in response. The aim of the present study was to determine whether individual differences in the subjective experience of rewarding and aversive effects of alcohol are a specific manifestation of general differences in reward and punishment sensitivity. Eighty-nine participants ( M age = 22.4, SD = 1.9; 47.2% women) consumed a moderate dose of alcohol, i.e., peak breath alcohol concentration (BrAC) ≈ 0.080 g%, and rated their level of stimulation and sedation at seven timepoints over the BrAC curve. Sensitivity to reward and punishment were assessed by a self-report questionnaire prior to consumption. Multilevel growth models showed that post-consumption changes in stimulation ratings varied as a function of participants' level of reward and punishment sensitivity. Drinkers more sensitive to reward reported feeling more stimulated shortly after drinking and exhibited an attenuated rate of decline in stimulation over the blood alcohol curve, relative to drinkers with less strong reward sensitivity. Reward sensitivity was not related to subjective ratings of sedation, and punishment sensitivity was not related to either stimulation or sedation ratings. Findings suggest that reward sensitivity may increase risk for alcohol misuse among young adult social drinkers by increasing their subjective feelings of stimulation while drinking. Highlights: Tested how reward and punishment sensitivity affects subjective alcohol response Reward hypersensitivity related to greater, more protracted feelings of stimulation Punishment sensitivity was unrelated to feelings of sedation after drinking. Drinkers hypersensitive to reward are more receptive to rewarding alcohol effects.